Urachal adenocarcinoma: a rare clinical presentation - Pastorello, Julia; Lando, Emanuela; Ractz Bueno, Marina; dos Santos do Amaral, Camila; Cechetti, Cristiane Pagnussat (Brazilian Journal of Case Reports, 2021)
Urachal tumor is extremely rare, since it is responsible for about 0.01% of all neoplasms already repeated in the history of clinical oncology, with the adenocarcinoma subtype being the most prevalent. Thus, the present work aims to report a case of a 55-year-old patient diagnosed with urachal tumor, relating the clinical presentation of the case according to current literary data. It was possible to show that such a diagnosis, as well as the institution of a standard treatment, is still a clinical challenge in modern medical practice.